The Office Of Religious Affairs As A Marriage Registration Agency For All Religions (Study Of The Office Of Religious Affairs In Medan Selayang) - Sembiring, Idha Aprilyana; Barus, Utary Maharany; Yefrizawati; Agusmidah; Mulhadi; Yati Sharfina D; Putri Rumondang Siagian (Mahadi: Indonesia Journal of Law, 2025)
The Office of Religious Affairs (KUA) is a government agency with the authority to register marriages among Muslims. For those who marry according to Islam, the registration is carried out at the KUA together with the marriage ceremony. Currently, there is a proposal to expand the role of the KUA as a marriage recorder not only for Muslims but for all religions proposed by the Minister of Religion. This proposal certainly raises pros and cons from various parties, both in society, government officials and religious leaders.. This research was conducted using a normative legal research method by searching for literature materials, both primary, secondary and tertiary legal materials related to this research study. This research was conducted to examine the urgency of revitalizing the role of the KUA as an institution for registering marriages for all religions and how the realization of this KUA role is with the revitalization of the role of the KUA. From the research conducted, the urgency of revitalizing the role of the KUA is related to efficiency in implementing marriage registration, but in terms of realization it is still difficult to do because many aspects must be restructured if the KUA is to be the only institution for registering marriages for all religions